A parent gesture intervention as a means to increase parent declarative pointing and child vocabulary. (29th June 2021) - Choi, Boin; Rowe, Meredith L.
Abstract: This study examined whether a brief parent gesture training resulted in a change in the communicative intent of pointing gestures used by parents of infants from age 10–12 months and whether specific types of points (declarative vs. imperative) were more or less likely to predict later child language skill at 18 months. Compared to parents who were randomized to the control group, parents in the intervention group produced significantly more declarative pointing gestures as a result of the intervention. Moreover, parents' use of declarative points at 12 months was predictive of later child vocabulary comprehension at 18 months. These findings suggest that a short‐term parent training can have important effects on the communicative intentions conveyed through gesture which predict vocabulary development.